Study on acute transfusion related adverse reactions in surgery department - Rahim, Rejla; Varghese, Sheela; Thambi, Renu; Suma, M. S. (International Journal of Research in Medical Sciences, 2021)
Background: Blood transfusion is a routine life- saving medical intervention which is generally regarded as safe when done appropriately. Without blood transfusion, many medical and surgical conditions like anemia, road traffic accidents, obstetric hemorrhage, cardiothoracic surgeries are nearly impossible to manage. However, this life-saving procedure is often associated with adverse effects ranging from minor chills and rigors to life-threatening anaphylaxis. Incidence of transfusion reactions is estimated at 0.001% -10%. The knowledge about the adverse transfusion reaction (ATRs) will help in early identification, management, and prevention of adverse transfusion reactions. Methods: Descriptive cross-sectional study done in 1047 patients, admitted and received at least one unit of whole blood and blood components in the surgery department, Government Medical College, Kottayam during the study period. Information regarding the issue of blood component collected from the transfusion medicine department and the details of the reactions were collected from the patients, and the transfusion reaction workups were done in the transfusion medicine department. The collected data was analysed using Microsoft Excel sheets. Results: The frequency of acute transfusion reaction in this study is 1%. The majority of the reactions were seen with a packed PRBC transfusion. Febrile non-hemolytic transfusion accounted for 54.64% followed by allergic reactions (36.36%) and Transfusion associated cardiac overload (9%). Conclusions: The frequency of ATR in our study was 1%. Febrile non-hemolytic transfusion (FNHTR) and allergic reactions were common patterns followed by transfusion associated cardiac overload (TACO) seen.